Pengaruh Debt Covenant, Profitability, Exchange Rate, Mekanisme Bonus Pada Transfer Pricing - Hepi Prayudiawan; Jodie Dwi Pamungkas (Akuntabilitas, 2020)
This study aims to analyze the effect of Debt Covenant, Profitability, Exchange Rate, and Bonus Mechanisms on the company’s decision to do Transfer Pricing. The independent variable in this study is transfer pricing which is proxied by the sale of related parties. The independent variables in this study are Debt Covenant, Profitability, Exchange Rate, and Bonus Mechanisms. This study used data from financial statements or annual reports of companies listed on the Indonesia Stock Exchange. The population of this study are all companies listed on the Indonesia Stock Exchange except for finance sector in 2016-2018. The results of the analysis of this study indicated that the Profitability variable influences the company’s decision to do Transfer Pricing, while Debt Covenant, Exchange Rate and Bonus Mechanism indicated that the variable did not affect the company’s decision to do Transfer Pricing